THE INFLUENCE OF CORPORATE REPUTATION AND MARKET COMPETITION ON COMPANY’S GROSS PROFIT - MIHAELA CORNELIA SANDU (Challenges of the Knowledge Society)
To have a profitable business you have to make a big effort. There are two important things that can influence the profitability of a company: the rivalry among stakeholders or market competition and an important intangible asset, corporate reputation. In this paper I will develop a study about how reputation and competition influence the market position of an important cosmetics business from Romania.